2015
DOI: 10.1002/chem.201406514
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Bridge in Photoinduced Electron Transfer in Porphyrin–Fullerene Dyads

Abstract: The role of π-conjugated molecular bridges in through-space and through-bond electron transfer is studied by comparing two porphyrin-fullerene donor-acceptor (D-A) dyads. One dyad, ZnP-Ph-C60 (ZnP = zinc porphyrin), incorporates a phenyl bridge between D and A and behaves very similarly to analogous dyads studied previously. The second dyad, ZnP-EDOTV-C60, introduces an additional 3,4-ethylenedioxythienylvinylene (EDOTV) unit into the conjugated bridge, which increases the distance between D and A, but, at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…Figure 4Dalso shows the decay component spectra of TP-C11-S-MPC obtained by global fitting of the transient absorption data to af our-exponential model. [15] Thed ecay component spectra of TP-Cn-X-MPC are shown in Figure S33. Am odel with four exponents was needed to obtain reasonable sigma values and consistent fits at all wavelengths, and resulted in two pairs of decay component spectra indicating the formation of at ransient band at l = 520 nm (1.7 ps and 21 ps) and asubsequent decay (590 ps and 13 ns).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 4Dalso shows the decay component spectra of TP-C11-S-MPC obtained by global fitting of the transient absorption data to af our-exponential model. [15] Thed ecay component spectra of TP-Cn-X-MPC are shown in Figure S33. Am odel with four exponents was needed to obtain reasonable sigma values and consistent fits at all wavelengths, and resulted in two pairs of decay component spectra indicating the formation of at ransient band at l = 520 nm (1.7 ps and 21 ps) and asubsequent decay (590 ps and 13 ns).…”
Section: Methodsmentioning
confidence: 99%
“…The method is described elsewhere. 25,26 Briefly, the decays at all wavelengths were fitted to a sum of exponents with the same time constants, but the pre-exponential factors were allowed to vary from wave- length to wavelength. A home-written program was used for this type of data analysis.…”
Section: Analysis Of Time Resolved Spectroscopy Datamentioning
confidence: 99%
“…The fullerene singlet state has a minor band around 1050 nm, that is less pronounced in intensity and shifted to the red compared to the anion radical. The signal for the singlet excited state can be difficult to discriminate from the C − 60 signal, if they cannot be observed separately 26. However, the intersystem crossing is an effective pathway for the fullerene singlet excited state relaxation, and the energy transfer from the excited QD to the fullerene moiety would eventually lead to the formation of a fullerene triplet excited state, that should show an absorption in the 700-800 nm region [42][43][44].…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Their photophysical properties have been investigated in details, revealing that the deactivation scenario can be affectedb ys everal parameters, such as the polarity of the solvent [15][16][17][18][19][20][21][22][23] or the interchromophoric distance. [24][25][26][27][28][29][30][31][32] As part of this research, it has been shown that the fullerene-porphyrin conjugation can be convenientlya chieved by using copper-catalyzed alkyne-azide cycloaddition (CuAAC) reactions. [29,[33][34][35][36][37][38][39][40][41][42][43] For example, we have reported the synthesis of the hybrid system fullerene-porphyrin-fullerene( F-P-F,s ee the structure below).T his compoundwas prepared by the reactiono faC 60 derivative bearing an azide functional group …”
Section: Introductionmentioning
confidence: 99%